Living With (out) Borders: Catholic Theological Ethics on the Migrations of Peoples - Vettikuzhiyil, Roy (Journal of Dharma, 2016)
Agnes M. Brazal and Maria Teresa Davila, eds., Living With (out) Borders: Catholic Theological Ethics on the Migrations of Peoples, New York: Orbis Books, 2016, pages 260, ISBN: 978-162698-166-9.